Synthesis of zeolite ferrierite from rice husk ash, characterization and activity towards friedel-crafts acylation for the formation of p-methoxypropiophenone - Bahruji, Hasliza (2005)
Rice husk ash (RHA) consisting more than 90% of amorphous silica obtained under controlled burning of rice husk was directly used in the synthesis of ferrierite type-zeolite. The synthesis was performed under hydrothermal condition in the presence of different organic templates, oxide compositions and at various crystallization periods. Solid products obtained from the synthesis were characterized by XRD, FTIR, 29Si MAS NMR, N2 (g) adsorption and SEM techniques. Results showed that pure ferrierite can be formed from the initial molar oxide ratios in the range of 1.31 – 1.5 Na2O : Al2O3 : 10 – 30 SiO2 : 4 – 10.0 template : 410 H2O with only pyrrolidine (Py) as the organic template. In general, quartz was obtained at higher SiO2/Al2O3 and lower Py/Al2O3 ratios. The crystal phase changes from ferrierite to analcime and lastly to quartz, with increasing SiO2/Py ratios. RHA was directly transformed to ferrierite phase within one day and reached equilibrium after 4 days crystallization. The acidity study of the H-ferrierite samples at different SiO2/Al2O3 ratios (12, 20 and 30) using IR-pyridine adsorption method showed the increase of acid sites with the decrease of SiO2/Al2O3 ratios in ferrierite framework. In each case, the Brønsted acid site is higher than Lewis acid sites. The catalytic activity of ferrierite at different SiO2/Al2O3 ratios towards Friedel-Crafts reaction between anisole and acid anhydrides was investigated. Results from the catalytic activity showed that only p-methoxypropiophenone and propionic acid was produced as the main product and side product respectively when propionic acid was used as acylating agent. The optimum temperature for the reaction was 120oC and ferrierite catalyst with SiO2/Al2O3 ratio 12 gave the highest conversion of anisole (66 %) and the selectivity of the main product (80 %). When acetic anhydride was employed as acylating agent, the conversion of anisole (55 %) and the selectivity of desired product (98 %) showed a higher percentage as compared with propionic anhydride. In both cases, the main product obtained is in para orientations with higher selectivity proved that H-ferrierite is a selective catalyst for the production of para orientation products